2017
DOI: 10.3847/1538-3881/153/2/51
|View full text |Cite
|
Sign up to set email alerts
|

The Pan-Pacific Planet Search. Vi. Giant Planets Orbiting Hd 86950 and Hd 222076

Abstract: We report the detection of two new planets orbiting the K giants HD 86950 and HD 222076, based on precise radial velocities obtained with three instruments: AAT/UCLES, FEROS, and CHIRON. HD 86950b has a period of 1270±57 days at a = 2.72±0.08 AU, and m sin i = 3.6±0.7 M Jup . HD 222076b has P = 871±19 days at a = 1.83±0.03 AU, and m sin i = 1.56±0.11 M Jup . These two giant planets are typical of the population of planets known to orbit evolved stars. In addition, we find a high-amplitude periodic velocity sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 77 publications
5
45
0
Order By: Relevance
“…Typically, the RV jitter is at the level of ∼ 0.5 m/s in dwarfs, ∼ 1.5 m/s in subgiants, ∼ 4 m/s in low-luminosity red giants (ν max close to 100 µHz) , ∼ 7 m/s in red clump stars (ν max close to 40 µHz), and ∼ 15 m/s in high-luminosity red giants (ν max close to 10 µHz). Encouragingly, these values are consistent with observed jitter values for stars in similar evolutionary states (Johnson et al 2010;Jones et al 2013;Wittenmyer et al 2016Wittenmyer et al , 2017.…”
Section: Predicting Rv Jitter From Stellar Parameterssupporting
confidence: 89%
“…Typically, the RV jitter is at the level of ∼ 0.5 m/s in dwarfs, ∼ 1.5 m/s in subgiants, ∼ 4 m/s in low-luminosity red giants (ν max close to 100 µHz) , ∼ 7 m/s in red clump stars (ν max close to 40 µHz), and ∼ 15 m/s in high-luminosity red giants (ν max close to 10 µHz). Encouragingly, these values are consistent with observed jitter values for stars in similar evolutionary states (Johnson et al 2010;Jones et al 2013;Wittenmyer et al 2016Wittenmyer et al , 2017.…”
Section: Predicting Rv Jitter From Stellar Parameterssupporting
confidence: 89%
“…Firstly, giant planets are generally hard to be formed around metal-poor stars. The RV surveys focusing on evolved stars (Reffert et al 2015, Jones et al 2016and Wittenmyer et al 2017) showed a positive correlation between stellar metallicity and occurrence rate of giant planets, which has been already observed for the cases of main-sequence stars Valenti 2005 andSantos 2007). This is consistent with one of the well-established planet formation scenario, core-accretion model (e.g., Pollack et al 1996).…”
Section: Discussionsupporting
confidence: 71%
“…A role of metallicity in planetary formation and evolution is not well investigated for evolved stars. While Reffert et al (2015), Jones et al (2016) and Wittenmyer et al (2017) showed that metalrich giant stars preferentially host giant planets, Jofré et al (2015) showed that there is no difference in metallicity between giant stars with and without planets. Jofré et al (2015) also showed that the metallicity of evolved stars hosting multiple-planets is slightly enhanced compared with evolved stars hosting single-planet, which was suggested for main-sequence stars (Wright et al 2009).…”
Section: )mentioning
confidence: 99%
“…However, while it is clear that stars with properties that deviate vastly from solar should not be used in differential analysis, it is not clear what the cut-off in parameters should be for planet host stars, which are typically FGK dwarfs and subgiants, although planets have also been found around giant stars (e.g. Wittenmyer et al (2017)). In this paper we analyse a set of 23 FGK stars and compare a line list us-ing the laboratory data from VALD with a differential line list in order to investigate if the differential list is really the best one to use and if errors are more likely for stars with parameters furthest from solar.…”
Section: Introductionmentioning
confidence: 99%